1987
DOI: 10.1104/pp.83.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Net CO2 Assimilation Rate of Grapevine Leaves in Response to Trunk Girdling and Gibberellic Acid Application

Abstract: Net CO2 assimilation rate (A), stomatal conductance (g,), and weight per unit leaf area (W) were determined on Thompson Seedless grapevines grown in the field. Treatments included fruit set applications of gibberellic acid (40 milligrams gibberellic acid (GA3) per liter) to vines, shoots and clusters, alone and in combination with trunk girdling. Leaf A and g, were measured prior to and 3, 6, and 13 days after fruit set. Weight per unit leaf area was determined on leaves collected subsequent to gas exchange me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
3
16
1
Order By: Relevance
“…The magnitude of differences in leaf TNC concentration among treatments were similar to differences in weight per unit leaf area measured in a previous study (8). One (2) with broadbean and may indicate the involvement of GA3 in sugar translocation.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The magnitude of differences in leaf TNC concentration among treatments were similar to differences in weight per unit leaf area measured in a previous study (8). One (2) with broadbean and may indicate the involvement of GA3 in sugar translocation.…”
Section: Discussionsupporting
confidence: 63%
“…Other information as given in Figure 1 and Table 1. previous experiment conducted on field-grown vines (8). The effects of the four treatments on leafA were opposite to their effects on leafTNC during that time period.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the TSS values, it was observed that girdling treatments accelerates ripening. Our results are in agreement with the findings of [17,[24][25][26][27][28].…”
Section: Resultssupporting
confidence: 83%